2019
DOI: 10.15407/dopovidi2019.09.088
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the creation of neuroprotective antiinflammatory drugs

Abstract: Сосудистые заболевания головного мозга-одна из главных причин заболеваемости, смертности и инвалидизации населения стран Евросоюза, США и Японии. Ежегодно в мире переносят инсульт около 6 млн человек. Увеличение распространенности инсульта наблюдается у лиц работоспособного возраста-до 60 лет. Согласно международным эпидемиологическим исследованиям, в мире от инсульта ежегодно умирает 4,7 млн человек. В большинстве промышленно развитых стран инсульт занимает 2-3 место в структуре общей смертности населения, ус… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 5 publications
0
7
0
4
Order By: Relevance
“…In particular, during the last 10-15 years, the positive effect of glycolysis substrates (fructose-1,6-diphosphate, phosphoenolpyruvate, hexose phosphate, etc. ), tricarboxylic acid cycle (succinate, malate, alpha-ketoglutarate), creatine phosphate, glutamic and aspartic amino acids and other drugs of the metabolite type (Chekman et al, 2016).…”
Section: Basic Aspects Of the Use Of Metabolites In Pharmacotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, during the last 10-15 years, the positive effect of glycolysis substrates (fructose-1,6-diphosphate, phosphoenolpyruvate, hexose phosphate, etc. ), tricarboxylic acid cycle (succinate, malate, alpha-ketoglutarate), creatine phosphate, glutamic and aspartic amino acids and other drugs of the metabolite type (Chekman et al, 2016).…”
Section: Basic Aspects Of the Use Of Metabolites In Pharmacotherapymentioning
confidence: 99%
“…In recent years, the direction associated with the correction of metabolism due to biotechnological synthesis and the use of modulators of endogenous bioreg-ulators has been intensively developing (Chekman et al, 2016). Successes in this area are associated with the discovery and detailed study of such compounds as modulators of endothelial synthesis of NO, calcitonin-gene-related peptide, calmodulin, vasoactive, intestinal polypeptide, urocortin -an endogenous polypeptide with anti-ischemic activity and a number of other biologically highly active and selectively acting peptides.…”
Section: Basic Aspects Of the Use Of Metabolites In Pharmacotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Зокрема, за порушень біоенергетики міокарда в останні 10-15 років виявлено позитивний ефект субстратів гліколізу (фруктозо-1,6-дифосфат фосфоенолпіруват, гексозофосфат та ін. ), циклу трикарбонових кислот (сукцинат-, малат-, альфа-кетоглутарат), креатинфосфату, глутамінової та аспарагінової амінокислот та інших препаратів типу метаболітів (Chekman et al, 2016).…”
Section: основні аспекти використання метаболітів у фармакотерапіїunclassified
“…As a proof of this hypothesis, the quantum mechanical energy descriptors of the boundary molecular orbitals were calculated at the Department of Medical Informatics, ZSMU: the energy of the highest occupied molecular orbital (E HOMO ) and the energy of the lowest unoccupied molecular orbital (E LUMO ) in the WinMopac software package (ver 7.2, descriptors -HOMOEnergy, LUMOEnergy, the semi-empirical method AM1, with the settings: Calculation = SinglePoint, WaveFunction = ClosedShell (RHF). As a result, it was found that they show that the E HOMO parameter (HOMOEnergy descriptor) at the largest degree affects the value of AOA [33][34] The mechanism of interaction of the C-3 substance and NO can be performed by transferring an electron from the highest occupied molecular orbital of the "spin trap" to the lowest unoccupied molecular orbital of the radical with the formation of a more stable radical complex.…”
mentioning
confidence: 99%